Changes in Stock Markets Interdependencies as a Result of the Global Financial Crisis: Empirical Investigation on the CEE Region - Tudor, Cristiana (Panoeconomicus, 2011)
This paper investigates causal relationships and short-term interaction mechanisms among six Central and Eastern European stock markets and the USA stock exchange, while paying special consideration to the effects of the 2007-2009 global financial crisis. We employ daily observations for the six CEE stock indexes and also for the US market covering the period January 2006-March 2009, which is subsequently divided into two sub-periods corresponding to the pre-crisis and crisis period. The study reveals that the relationships among CEE stock markets are time varying. While before the crisis stock market linkages are limited, we find that during crisis these interactions become significantly stronger. Our results further suggest that the potential for diversifying risk by investing in different CEE markets is limited during financial turmoil. Other findings reveal the leading role of the Russian market in the CEE region before the crisis. Also, before the crisis CEE markets were significantly influenced by innovations in the USA market, thus explaining why they were affected heavily by the crisis, which has managed to spread immediately in the region. Key words: VAR analysis, Granger causality, Impulse response, Crisis, CEE stock markets. JEL: C32, F36, G15.